2004
DOI: 10.1063/1.1644146
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the inverted temperature gradient phenomenon on the condensation coefficient

Abstract: This Brief Communication considers the effect of the condensation coefficient on the inverted temperature gradient phenomenon in a two-plate geometry, assuming diffuse reflection at the interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Comparison with Eqs. (26) and (28) indicates that for the Maxwellian case R 11 −1 = R 22 −1 = 1 and R 12 −1 = R 21 −1 = 0, so that in this case R is the unit matrix.…”
Section: B Mass and Energy Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison with Eqs. (26) and (28) indicates that for the Maxwellian case R 11 −1 = R 22 −1 = 1 and R 12 −1 = R 21 −1 = 0, so that in this case R is the unit matrix.…”
Section: B Mass and Energy Fluxmentioning
confidence: 99%
“…A popular configuration for studying one-dimensional evaporation and condensation phenomena is the parallel surface geometry [7,8,21,[25][26][27][28], a topic that goes beyond the scope of this paper and will not be further discussed. Another interesting recent approach to the topic is the Van der Waals square gradient model [29][30][31], which also shall not be discussed further.…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been found that the KBC significantly affects the macroscopic variables obtained from Eq. (1) [8,9] during net evaporation and condensation, the proper specification of the KBC at the interface is critical. One of the most conventional forms of the KBC is shown as follows:…”
Section: Introductionmentioning
confidence: 99%
“…12,26,30 Moreover, theoretical study was conducted on these phenomena, and the threshold of the occurrence was reported. 31 Negative mass flows were investigated by Onishi 29 (but never occurred in the present simulation). Detailed explanations of these phenomena are beyond the scope of this study.…”
mentioning
confidence: 99%